Implementation of Discovery Learning Model using Educative Game to Improve Students’ Learning Outcomes - Albab, Moh. Ulul; Hadi, Wiwin Puspita; Rumyah, Siti (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
Discovery learning model is one of innovative learning models that enable students to build and enrich their knowledge by searching new information through investigations and observations. This learning model is appropriate to be implemented in the science learning process to facilitate students in comprehending the concepts easily. This study aims to describe students’ learning outcomes after the implementation of the discovery learning model using educative game. This type of research is a classroom action research that is implemented in two cycles, each cycle is divided into four stages, i.e., Planning, Action, Observation, and Reflection. The research was conducted in the odd semester of the 2023/2024 academic year at SMP Negeri 1 Tanjungbumi, toward the students of class VIII A. The instrument of the retrieval was a written test of excretion system consisting of 20 questions. The results of the study showed that in cycle 1 the pre-test results obtained an average score of 52.69 and a percentage of completion of 44.00% and the post-test obtained an average score of 55 and a percentage of completion of 43.00%. Furthermore, in cycle 2 the pre-test results obtained an average score of 76 and a percentage of completion of 68% and when carrying out the post-test obtained an average score of 79 and a percentage of completion of 83%. To conclude, the implementation of the discovery learning model using educative game can improve student learning outcomes in the topic of excretion system